Molecular Docking Study for Binding Affinity of 2H-thiopyrano[2,3-b]quinoline Derivatives against CB1a - Sharma, Shivangi; Singh, Shivendra (Interdisciplinary Perspectives on Infectious Diseases, 2023)
Quinoline-based molecules are major constituents in natural products, active pharmacophores, and have excellent biological activities. Using 2H-thiopyrano[2,3-b]quinoline derivatives and CB1a protein (PDB ID: 2IGR), the molecular docking study has been revealed in this article. The study of in silico molecular docking analysis of such derivatives to determine the binding affinity, residual interaction, and hydrogen bonding of several 2H-thiopyrano[2,3-b]quinolines against CB1a is reported here. The current work demonstrated that 2H-thiopyrano[2,3-b]quinoline derivatives could be effective antitumor agents to produce potent anticancer medicines in the near future.